Comparison of Wolbachia Knowledge between High School Students in Suburban and Urban of Yogyakarta - Naufal Abdan Ammar; Tri Wulandari Kesetyaningsih (Jurnal Berkala Kesehatan, 2024)
Dengue hemorrhagic fever is a health problem throughout the world. The problems mainly originate from the control that still need to be improved. The Indonesian government’s latest control is the Wolbachia program which was initiated in Yogyakarta Province, especially in Sleman Regency and Yogyakarta City. This research aims to determine the knowledge about Wolbachia program among the students in Sleman Regency (sub-urban) and Yogyakarta City (urban). This is an observational study with a cross-sectional design. Research sampling was carried out using the purposive sampling method. The study involved 181 High School students in Sleman Regency and 200 students in Yogyakarta City. Data collection conducted using questionnaire. The average score for Sleman Regency students is 46.85 and Yogyakarta City students 47.77, means low. Mann-Whitney analysis proved that there is no difference in the knowledge about Wolbachia program between sub-urban and urban students (p = 0.273). Male students' scores were lower in urban and female students' scores were lower in sub-urban. Socialization about the Wolbachia program needs to be carried out targeting students.